PENGARUH PRIORITAS PENGGUNAAN DANA DAN MENTAL ACCOUNTING TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PENERIMA KIP-K (Studi Kasus Pada Mahasiswa Penerima KIP-K Undana Angkatan 2021) - Martha Helena Dai Samon (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2026)
The Indonesian government launched the KIP-K scholarship program as an initiative to expand access to higher education for high-achieving students from low-income families. Nusa Cendana University (UNDANA) is recognized as one of the universities with the highest number of KIP-K scholarship recipients nationwide. Although this program provides significant financial benefits, there have been instances of fund misuse by some students, leading to negative perceptions among non-recipient students. This study employs a quantitative approach utilizing various statistical analysis techniques, including validity and reliability testing, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The research sample consists of 95 KIP-K scholarship recipients from UNDANA's 2021 cohort. The study aims to examine the influence of fund usage priorities and mental accounting on the financial management of KIP-K scholarship recipients. The findings reveal that: (1) fund usage priorities significantly affect the financial management of KIP-K recipients, (2) mental accounting impacts their financial management, and (3) both fund usage priorities and mental accounting simultaneously influence the financial management of KIP-K scholarship recipients. Keywords: Fund Usage Priority, Mental Accounting, Financial Management